2021
DOI: 10.18632/aging.202891
|View full text |Cite
|
Sign up to set email alerts
|

E2F2 inhibition induces autophagy via the PI3K/Akt/mTOR pathway in gastric cancer

Abstract: Background: E2F2 is a member of the E2F transcription factor family and has important but not fully understood biological functions in cancers. The biological role of E2F2 in gastric cancer (GC) also remains unclear. Methods: We examined the expression levels of E2F2 in GC using publicly available datasets such as TIMER, Oncomine, GEPIA, UALCAN, etc., and in our patient cohort, using quantitative real-time PCR, western blotting, and immunohistochemistry. We further investigated the effects of E2F2 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…34 E2F2 was highly expressed in both gastric cancer tissues and cells compared with normal gastric tissues/cells, which promoted the migration and invasiveness of gastric cancer cells. 35 It was also reported that the over-expressed miR-490-5p could inhibit the metastasis of hepatocellular carcinoma cells by down-regulating E2F2 expression levels. 36 In our research, no significant differences were seen in the expression of E2F2 between normal tissues and carcinoma tissues in patients.…”
Section: Discussionmentioning
confidence: 98%
“…34 E2F2 was highly expressed in both gastric cancer tissues and cells compared with normal gastric tissues/cells, which promoted the migration and invasiveness of gastric cancer cells. 35 It was also reported that the over-expressed miR-490-5p could inhibit the metastasis of hepatocellular carcinoma cells by down-regulating E2F2 expression levels. 36 In our research, no significant differences were seen in the expression of E2F2 between normal tissues and carcinoma tissues in patients.…”
Section: Discussionmentioning
confidence: 98%
“…MYC is a core of the oncogenic process (29) and can promote tumorigenesis with its regulation of transcription (30). E2F plays a crucial role in the CDK- RB-E2F axis, the core transcriptional machinery to drive cell cycle progression (31). E2F2, a member of the E2F family, is a regulator in PI3K/Akt/mTOR pathway, which is strongly associated with autophagy for it inhibits autophagy in GC cells when overexpressed (31).…”
Section: Discussionmentioning
confidence: 99%
“…find that E2F2 accelerates autophagy in gastric cancer via modulating the PI3K/Akt/mammalian target of rapamycin (mTOR) pathway [ 28 ]. The latest study has elucidated that E2F2 drives glioma’s progression via the PI3K/Akt pathway in a 6-phosphofructo-2-kinase/fructose-2,6-biphosphatase 4 (PFKFB4)-dependent manner [ 29 ]. The results of the study further affirmed the vital role of E2F2 in modulating PI3K/Akt signal.…”
Section: Discussionmentioning
confidence: 99%